Comprehensive Assessment of Coronary Artery Disease in Sports-Related Sudden Cardiac Arrest. Issue 4 (24th July 2018) - Karam, Nicole; Pechmajou, Louis; Dumas, Florence; Bougouin, Wulfran; Sharifzadehgan, Ardalan; Beganton, Frankie; Bonnet, Guillaume; Jost, Daniel; Lamhaut, Lionel; Varenne, Olivier; Aubry, Pierre; Sideris, Georgios; et al.
Abstract : Supplemental Digital Content is available in the text.